Особливості відшкодування шкоди, завданої незаконними діями, рішеннями та бездіяльністю органів, що здійснюють оперативно-розшукову діяльність, досудове розслідування, прокуратури або суду - Курило, Тетяна Вячеславівна; Kurylo, Tetiana (ВД "Гельветика", 2019)
Аналіз юридичної літератури свідчить, що майновою або матеріальною вважається шкода, яка має певну економічну цінність і виражається в грошах. Види шкоди, що підлягають відшкодуванню, передбачені в Законі Україні «Про порядок відшкодування шкоди, завданої громадянинові незаконними діями органів, що здійснюють оперативно-розшукову діяльність, органів| досудового розслідування, прокуратури і суду» й у Положенні про застосування цього Закону, затвердженому Наказом Міністерства юстиції, Генеральної прокуратури та Міністерства фінансів України.

Analysis of legal literature shows that property or material is considered a harm, which has some economic value and is expressed in money. Kinds of damage to be compensated are stipulated in the Law of Ukraine “On the Procedure for Compensation of Damage Inflicted on Citizen by Illegal Actions of Bodies Performing Operative Investigation Activities, Authorities | pre-trial investigation, prosecutor's office and court” and in the Regulation on the application of this Law, approved by the order of the Ministry of Justice of the Prosecutor General's Office for the Ministry of Finance of Ukraine. Compensation for damage through the provision of a thing of the same kind and quality is applicable if, in the circumstances of the case, this way of reimbursement is possible. When compensation for damage in kind is not possible, the victim is compensated in full amount of damages in accordance with the real value at the time of consideration of the case of losing property. The cost of lost housing is reimbursed from market prices that are in effect at the time of the citizen's request for compensation for damage, if the property in question has not been retained in kind. The right to compensation for damage inflicted arises from the moment when the court acquits the acquittal, from the date of the ruling on the closure of the criminal proceedings, closure of the case about the administrative offense. Execution of court decisions, which provides for compensation for damage caused to the citizen by illegal actions of the inquiry, pre-trial investigation, prosecutor's office, and courts, is carried out by the State Treasury of Ukraine according to the requirements of the State Bailiff Service on the order of their receipt, at the expense and within the limits of the budget appropriateness of the approved in the State Budget of Ukraine for this purpose.
Курило Т. В. Особливості відшкодування шкоди, завданої незаконними діями, рішеннями та бездіяльністю органів, що здійснюють оперативно-розшукову діяльність, досудове розслідування, прокуратури або суду / Т. В. Курило // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. – Одеса : Гельветика, 2019. – Вип. 33. – С. 36-41.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; майнова шкода; відшкодування шкоди; незаконні рішення; дії чи бездіяльність; відповідальність; заподіяна шкода; property damage; indemnification; illegal decisions; actions or inactivity; responsibility; damage